Study the effect of foliar spraying with different levels of urea in some anatomical side for eggplant Solanum melongena L. - Sajid S. Saleem; Hibba F. Abdul Fatah; Rassmy M. Hamad (مجلة جامعة الانبار للعلوم الصرفة, 2014)
The field experiment had been conducted in the Lath-house in the college of Agriculture , Anbar University by planting Solanum melongena L. Black beauty during agricultural season of 2010. Seedlings were distributed randomly according to complete randomized design (CRD) . The four concentrations of urea dissolved in distill water . The levels of urea were control (N0) ; 0.5 g/L(N1) ;1 g/L(N2);8 g/L(N3) . After 40 days of transplanting Eggplants were sprayed four times by urea concentrations . Anatomic study of cross-sections of root showed clear reduction in thickness of Epidermis, cortex and xylem tissues of plants treated with the concentration 8 gram urea/L where thickness of these tissues was 26.07 µm, 178.52 µm, 37.60 µm respectively. The phloem showed 224.32 um thickness. It was the highest among other treatments especially the treatment 1g urea/L which showed higher rate of xylem thickness of 373.68 µm. The cross-section of stem also showed clear difference in the epidermis thickness for all treated plants. In addition, 1gram urea/L showed higher cortex thickness of the stem,( 432.93 µm). Increasing urea concentration to 8 gram/L lead to reduce xylem thickness (104.72 µm) and decreasing pith thickness in the same treatment rated 426.67 µm. Plants treated with 1 gram urea/L, show increasing in the phloem and the pith thickness of 98.62 µm, 577.47µm rate respectively.The study showed that stoma distribution in the surface of leaves is of Anomocytic type with clear reduction of the outer epidermis thickness of 1gram urea/L treatment rated 16.05µm. This treatment showed highest rate in palasid tissues 98.40. The N2 treatment shows higher rate in stoma frequency on the upper and lower surfaces, 10 stoma/ml². The N3 treatment shows less number of stoma on the upper and lower surfaces, 6.04 stoma/ml². As for cell length in the two epidermis, the N2 treatment shows clear increase rated 59.08 in comparison with control treatment and othertreatments.